PERSEPSI PESERTA DIDIK KELAS XII IPS TENTANG KETERAMPILAN MENGAJAR GURU GEOGRAFI DI SMA NEGERI 2 KOTA SOLOK - Rima Syintia; Ernawati Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to determine the perceptions of students in class XII IPS about the teaching skills of geography teachers at SMA Negeri 2 Kota Solok in opening and closing lessons, teaching skills in asking questions, teaching skills in providing reinforcement, teaching skils in class management, teaching skills in conducting variety, teaching skills in explaining lessons, and teaching skills in guiding small group discussions. This type of research is descriptive qualitative. Data analysis using qualitative data analysis. Techniques in collecting data using the interview method. The population in this study were students of class XII IPS using purposive sampling technique. The results of this study indicate that (1) students perceptions of class XII IPS about teaching skills of geography teachers at SMA Negeri 2 Kota Solok in opening and closing lessons can be categorized as good(2) teaching skills in questioning are categorized as quite good(3) teaching skills in giving strengthening is categorized as good(4) teaching skills in managing the class are categorized as good(5) teaching skills in conducting variations as categorized as good enough(6) teaching skills in explaining lessons are categorized quite good, and (7) teaching skliis in guiding small group discussions are categorized good.